Multi-dimensional nano-based functional material for oil well cement

By using multi-dimensional nano-based functional materials in oil and gas well cementing, combining the different dimension characteristics of nanomaterials and multiple surface treatment modification technology, the problem of limited application of nanomaterials in oil and gas well cementing is solved, and the nano-effect is fully realized The performance and the performance of cement stone have been significantly improved.

CN119430710AActive Publication Date: 2025-02-14CHINA NAT PETROLEUM CORP +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310938844.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-28
Publication Date
2025-02-14
Estimated Expiration
2043-07-28

AI Technical Summary

Technical Problem

The application of existing nanomaterials in oil and gas well cementing is limited, and the main problems include the inability to effectively exert nanoeffects, thickening problems, complex production processes and high costs.

Method used

Using multi-dimensional nano-based functional materials, through the organic combination of two-dimensional, one-dimensional and zero-dimensional nanomaterials, various dimensional structural characteristics are utilized, and multiple surface treatment modification technology are combined to avoid nanoparticles agglomeration, give full play to the nano-effect, and improve flow. Variable performance.

Benefits of technology

It has achieved effective performance of nanomaterials in cement slurry, significantly shortened the waiting time, reduced the risk of traversing flow, improved the early and late strength of cement stone, improved toughness, and simple production process and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430710A_ABST
    Figure CN119430710A_ABST
Patent Text Reader

Abstract

The invention discloses a multi-dimensional nano-based functional material for oil well cement. The multi-dimensional nano-based functional material comprises dispersion liquid of a two-dimensional nano-material, dispersion liquid of a one-dimensional nano-material and dispersion liquid of a zero-dimensional nano-material. The mass ratio of the dispersion liquid of the two-dimensional nano material to the dispersion liquid of the one-dimensional nano material to the dispersion liquid of the zero-dimensional nano material is 5: 3: 2. The solid content of the dispersion liquid of the two-dimensional nano material is 15%-20%. The solid content of the dispersion liquid of the one-dimensional nano material is 5-10%. The solid content of the dispersion liquid of the zero-dimensional nano material is 15%-20%. In combination with engineering requirements, the nano-materials with different components in three dimensions are organically combined together, and the effects of the nano-materials in the aspects of promoting hydration and nucleation, improving mechanical properties and the like are fully exerted by utilizing the structural characteristics of various dimensions, so that the material simultaneously shows excellent functions of coagulation acceleration, channeling prevention, enhancement and the like, and shows the characteristic of multiple effects of one agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of oilfield cementing, and in particular to a multi-dimensional nano-based functional material for oil well cement. Background Art

[0002] As exploration and development progresses, the operating environment becomes increasingly complex and operating costs are gradually reduced, which brings severe challenges to cementing technology. How to reduce costs to the greatest extent on the basis of solving engineering problems is a hot topic in the research and development of new materials in the future. Traditional materials are difficult to meet the above requirements due to their own characteristics. Nanomaterials, because their scale is between microscopic and macroscopic objects, exhibit many special effects different from traditional materials and show great application potential in many industries.

[0003] At present, the research and application of nanomaterials in oil and gas well cementing is still in its infancy, and most of them are in indoor research, with few field applications. The main problems and difficulties limiting their application in oil and gas well cementing are as follows: (1) Nanomaterials are extremely small in size and are easy to agglomerate and difficult to disperse after agglomeration, resulting in the "nano effect" not being able to be effectively exerted, and the effect is not obvious after adding to cement slurry. (2) Nanomaterials have a large specific surface area, and they often cause severe thickening when added to cement slurry, limiting their addition and use effect. (3) Many nanomaterials have complex production processes and often only play a certain role, which leads to high cost and low performance, limiting their application under the low-cost strategy of oil and gas well engineering. Therefore, it is of great significance to develop multifunctional nanomaterials with low cost and good comprehensive performance suitable for oil and gas well cementing. Summary of the invention

[0004] The present application provides a multi-dimensional nano-based functional material for oil well cement, which can be used in cementing oil and gas wells.

[0005] This application adopts the following technical solutions:

[0006] The present application provides a multi-dimensional nano-based functional material for oil well cement, including a dispersion of a two-dimensional nanomaterial, a dispersion of a one-dimensional nanomaterial, and a dispersion of a zero-dimensional nanomaterial. The mass ratio of the dispersion of the two-dimensional nanomaterial, the dispersion of the one-dimensional nanomaterial, and the dispersion of the zero-dimensional nanomaterial is 5:3:2. The solid content of the dispersion of the two-dimensional nanomaterial is 15% to 20%. The solid content of the dispersion of the one-dimensional nanomaterial is 5 to 10%. The solid content of the dispersion of the zero-dimensional nanomaterial is 15% to 20%.

[0007] Furthermore, the dispersion of the two-dimensional nanomaterial includes a dispersion of nano calcium silicate and a dispersion of nano flaky aluminum oxide. The mass ratio of nano calcium silicate to nano flaky aluminum oxide is 3:1. The size of nano calcium silicate is 50 to 100 nm. The thickness of nano flaky aluminum oxide is 60 to 80 nm. The dispersion of nano calcium silicate is synthesized by solution precipitation method, and the raw materials and mass parts used for synthesis are: 20 to 50 parts of calcium nitrate, 10 to 30 parts of calcium chloride, 20 to 50 parts of sodium metasilicate, 10 to 30 parts of polycarboxylic acid dispersant, and 5 to 10 parts of sulfonated aldehyde ketone condensation polymer dispersant.

[0008] Furthermore, the one-dimensional nanomaterial includes an inorganic nanofibrous material and an organic nanofibrous material. The inorganic nanofibrous material is selected from one or a mixture of silicon nanowires, zinc oxide nanowires, silicon carbide, and carbon nanotubes. The organic nanofibrous material is selected from one or a mixture of nanocellulose and polyvinyl alcohol nanofibers. The mass ratio of the inorganic nanofibrous material to the organic nanofibrous material is 1:1. The diameter of the one-dimensional nanomaterial is 20 to 60 nm. The one-dimensional nanomaterial in the dispersion of the one-dimensional nanomaterial is treated with a silane coupling agent and a polycarboxylic acid dispersant, and the mass ratio of the silane coupling agent to the polycarboxylic acid dispersant is 2:1.

[0009] Furthermore, the zero-dimensional nanomaterial is selected from one or a mixture of nano-spherical silicon dioxide and nano-spherical aluminum oxide. The particle size of the zero-dimensional nanomaterial is 10 to 30 nm. The zero-dimensional nanomaterial in the dispersion of the zero-dimensional nanomaterial is surface treated with an amide copolymer containing amino and carboxyl groups, and the relative molecular weight of the amide copolymer containing amino and carboxyl groups is 120,000 to 150,000, and the molecular weight distribution index is 2.0 to 2.2.

[0010] Furthermore, the relative molecular weight of the polycarboxylic acid dispersant is 60,000 to 100,000, and the molecular weight distribution index is 1.5 to 1.7.

[0011] Compared with the prior art, this application has the following beneficial effects:

[0012] 1. Nanomaterial particles of different dimensions move in different directions and thus exhibit different characteristics. This application combines nanomaterials of three dimensions and different components organically in accordance with engineering needs, and utilizes the structural characteristics of various dimensions to give full play to their role in promoting hydration, nucleation and improving mechanical properties, so that the material simultaneously exhibits excellent functions such as promoting coagulation, preventing channeling, and enhancing, showing the characteristics of one dose with multiple effects.

[0013] 2. According to the characteristics of the material, multiple surface treatment modification methods such as polycarboxylic acid dispersants, sulfonated aldehyde ketone condensation dispersants, silane coupling agents and multi-branched amide copolymers containing amino and carboxyl groups are used to avoid the agglomeration of nanoparticles, so as to give full play to the nano effect and greatly increase the material efficiency.

[0014] 3. By introducing substances with large steric hindrance effects such as polycarboxylic acids, sulfonated aldehydes and ketones condensation products and carboxyl groups - multi-branched amide copolymers containing amino groups and carboxyl groups, a significant drag reduction effect is achieved, thereby avoiding the thickening problem of nanomaterials in cement slurry and showing the effect of improving rheology.

[0015] 4. By combining one-dimensional inorganic nanomaterials and one-dimensional organic nanomaterials, their respective characteristics can be fully utilized to significantly improve the mechanical properties of cement paste.

[0016] 5. The preparation process of multi-dimensional nano-based functional material products is simple, low-cost and easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a process flow chart for preparing the multi-dimensional nano-based functional material products in this application. DETAILED DESCRIPTION

[0018] The technical methods in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0019] The embodiment of the present application provides a multi-dimensional nano-based functional material for oil well cement, which is compounded by dispersions of three nanomaterials of different dimensions: a dispersion of a two-dimensional nanomaterial, a dispersion of a one-dimensional nanomaterial, and a dispersion of a zero-dimensional nanomaterial. The mass ratio of the dispersion of the two-dimensional nanomaterial, the dispersion of the one-dimensional nanomaterial, and the dispersion of the zero-dimensional nanomaterial is 5:3:2.

[0020] The dispersion of two-dimensional nanomaterials is compounded by mixing two dispersions of two-dimensional nanomaterials, namely, dispersion of nano calcium silicate and dispersion of nano flaky aluminum oxide. The solid content of the dispersion of two-dimensional nanomaterials is 15% to 20%, such as 15%, 18%, and 20%. The mass ratio of nano calcium silicate to nano flaky aluminum oxide is 3:1. The nanometer size of nano calcium silicate is 50 to 100 nm, such as 50 nm, 80 nm, and 100 nm. The sheet thickness of nano flaky aluminum oxide is 60 to 80 nm, such as 60 nm, 70 nm, and 80 nm.

[0021] Among them, the dispersion of nano calcium silicate is specifically a thin film dispersion of nano calcium silicate, which is synthesized by solution precipitation method, and the raw materials and mass parts used for synthesis are: 20-50 parts of calcium nitrate, such as 20 parts, 30 parts, and 50 parts; 10-30 parts of calcium chloride, such as 10 parts, 20 parts, and 30 parts; 20-50 parts of sodium metasilicate, such as 20 parts, 30 parts, and 50 parts; 10-30 parts of polycarboxylic acid dispersant, such as 10 parts, 20 parts, and 30 parts; 5-10 parts of sulfonated aldehyde ketone condensation polymer dispersant, such as 5 parts, 8 parts, and 10 parts. Specifically, the preparation method of the above-mentioned dispersion of nano calcium silicate includes the following steps:

[0022] (1) Provide the following raw materials in parts by weight: 20-50 parts of calcium nitrate, 10-30 parts of calcium chloride, 20-50 parts of sodium metasilicate, 10-30 parts of polycarboxylic acid dispersant, and 5-10 parts of sulfonated aldehyde ketone condensation polymer dispersant.

[0023] In the above steps, the polycarboxylic acid dispersant is composed of methacrylic acid as the main chain and a polyether with a certain side chain length grafted thereto, the relative molecular weight of the polycarboxylic acid dispersant is 60000-100000, and the molecular weight distribution index is 1.5-1.7. The sulfonated aldehyde ketone polycondensate dispersant is a conventional dispersant for oil well cement, and may also be other commercially available products, such as CF40S, which is not limited in this application.

[0024] (2) Add an appropriate amount of distilled water to a beaker, weigh the polycarboxylic acid dispersant and the sulfonated aldehyde ketone polycondensate dispersant, mix them evenly, pour them into a clean three-necked bottle, start stirring and keep the speed at 300±10r / min, such as 290r / min, 300r / min, 310r / min, then add the pre-prepared mixed solution of calcium nitrate and calcium chloride and the sodium metasilicate solution into two constant pressure dropping funnels respectively, then turn on the heating device and fill with nitrogen for protection. When the system temperature rises to 25°C, open the two dropping funnels at the same time to initiate the reaction. During the reaction, use sodium hydroxide solution or nitric acid solution to control the pH value of the system at 11-13, such as pH=11, pH=12, pH=13, and keep the temperature at 25-40°C, such as 25°C, 30°C, 40°C, and keep the constant temperature reaction for 6-10h, such as 6h, 8h, 10h, and then obtain a thin film of nano calcium silicate dispersion.

[0025] One-dimensional nanomaterials are compounded from two one-dimensional nanomaterials, inorganic nanofibrous materials and organic nanofibrous materials. Among them, the inorganic nanofibrous materials are selected from one or a mixture of silicon nanowires, zinc oxide nanowires, silicon carbide, and carbon nanotubes. For example, the inorganic nanofibrous materials are selected from silicon nanowires, and the inorganic nanofibrous materials are selected from a mixture of silicon carbide and carbon nanotubes. The organic nanofibrous materials are selected from one or a mixture of nanocellulose and polyvinyl alcohol nanofibers. For example, the organic nanofibrous materials are selected from nanocellulose, and the organic nanofibrous materials are selected from a mixture of nanocellulose and polyvinyl alcohol nanofibers. The mass ratio of inorganic nanofibrous materials and organic nanofibrous materials is 1:1. The diameter of the one-dimensional nanomaterials is 20 to 60 nm, such as 20 nm, 40 nm, and 60 nm.

[0026] The one-dimensional nanomaterial in the dispersion of the one-dimensional nanomaterial is treated with a silane coupling agent and a polycarboxylic acid dispersant, and the mass ratio of the silane coupling agent to the polycarboxylic acid dispersant is 2:1. Among them, the silane coupling agent can be prepared by an existing process, or it can be other commercially available products, such as KH550, which is not limited in this application. The requirements of the polycarboxylic acid dispersant are the same as above and are not repeated here. The solid content of the dispersion of the one-dimensional nanomaterial is 5 to 10%, such as 5%, 8%, 10%.

[0027] The zero-dimensional nanomaterial is selected from one or a mixture of nano-spherical silicon dioxide and nano-spherical aluminum oxide. For example, the zero-dimensional nanomaterial is selected from nano-spherical silicon dioxide, and the zero-dimensional nanomaterial is selected from a mixture of nano-spherical silicon dioxide and nano-spherical aluminum oxide. The particle size of the zero-dimensional nanomaterial is 10 to 30 nm, such as 10 nm, 20 nm, and 30 nm.

[0028] The zero-dimensional nanomaterial in the dispersion of the zero-dimensional nanomaterial is surface treated with an amide copolymer containing amino groups and carboxyl groups, the relative molecular weight of the amide copolymer containing amino groups and carboxyl groups is 120,000 to 150,000, and the molecular weight distribution index is 2.0 to 2.2. Among them, the amide copolymer containing amino groups and carboxyl groups is specifically a multi-branched amide copolymer containing amino groups and carboxyl groups, and the multi-branched amide copolymer containing amino groups and carboxyl groups can be prepared by existing processes. The solid content of the dispersion of the zero-dimensional nanomaterial is 15% to 20%, such as 15%, 18%, and 20%.

[0029] The multi-dimensional nano-based functional material for oil well cement of the present application belongs to a cement admixture used in the field of oil field cementing. It can not only improve the rheological properties of cement slurry while significantly shortening the waiting time and reducing the probability of crossflow, but also significantly increase the early and late strength of cement stone and improve the toughness of cement stone, and has the function of one dose with multiple effects.

[0030] See also Figure 1The embodiment of the present application provides a method for preparing the multi-dimensional nano-based functional material for oil well cement, comprising the following steps:

[0031] Prepare the above-mentioned film-like nano calcium silicate dispersion, then put the above-mentioned nano calcium silicate dispersion into an ultrasonic device, turn on the ultrasound and keep it for 20 minutes, then add the dispersion of nano flaky aluminum oxide at a mass ratio of 3:1 between nano calcium silicate and nano flaky aluminum oxide to obtain a dispersion of two-dimensional nanomaterials. Then gradually add the dispersion of one-dimensional nanomaterials and the dispersion of zero-dimensional nanomaterials to the dispersion of two-dimensional nanomaterials at a mass ratio of 5:3:2 among the dispersion of two-dimensional nanomaterials, the dispersion of one-dimensional nanomaterials and the dispersion of zero-dimensional nanomaterials, and keep the ultrasound for 30 to 60 minutes to obtain a multi-dimensional nano-based functional material product.

[0032] The multi-dimensional nano-based functional material for oil well cement prepared in the present application does not thicken the cement slurry, and can significantly shorten the waiting time and static gelling transition time, and significantly increase the anti-channeling ability of the cement slurry and the anti-destruction ability of the cement stone.

[0033] In general, the present application mainly solves the problem that the nano-effect of nano-materials in mud cannot be effectively exerted through two aspects. On the one hand, the synergistic effect of composite materials is fully exerted. First, by utilizing the characteristics of nano-materials of different dimensions, three-dimensional nano-materials are organically combined to give full play to the synergistic effect of nano-materials of each dimension; secondly, inorganic and organic nano-materials are organically combined to give full play to the synergistic effect of the two. On the other hand, a variety of surface modification methods are combined with ultrasonic dispersion to avoid the agglomeration of nano-materials, so as to maximize the nano-effect of nano-materials. Through the above means, the nano-effect of nano-materials in cement slurry can be fully exerted.

[0034] Since nanomaterials have a large specific surface area, they can easily cause the system to thicken. In order to solve the problem of traditional nanomaterials thickening in cement slurry, the present application uses polycarboxylic acids, sulfonated aldehyde ketone polycondensates and substances with large steric hindrance effects containing carboxyl groups - multi-branched amide copolymers containing amino groups and carboxyl groups to modify nanomaterials. These substances can enhance the nano effect and play a good drag reduction role in cement slurry, thereby avoiding the problem of nanomaterials thickening in cement slurry without affecting other properties of cement slurry.

[0035] In view of the problem that nanomaterials are complex to produce, have a single function and high cost, this application adopts solution precipitation method and composite modification to prepare multi-dimensional nano-based functional materials for oil well cement. The production process is simple, easy to industrialize and low cost. In combination with engineering needs, according to the characteristics of nanomaterials of different dimensions and different components, they are organically combined together, thus achieving the function of one dose with multiple effects, realizing the high efficiency of nanomaterials, and laying the foundation for their industrial application.

[0036] The following is a detailed description with reference to specific embodiments:

[0037] Example 1

[0038] Add an appropriate amount of distilled water to a beaker, weigh 30 parts of polycarboxylic acid dispersant and 5 parts of sulfonated aldehyde ketone condensation polymer dispersant, mix well, pour into a clean three-necked bottle, turn on stirring and keep the speed at 300±10r / min. Weigh 20 parts of calcium nitrate and 30 parts of calcium chloride and dissolve them in an appropriate amount of distilled water, weigh 50 parts of sodium metasilicate and dissolve them in an appropriate amount of distilled water, then add the prepared mixed solution of calcium nitrate and calcium chloride and sodium metasilicate solution to two constant pressure dropping funnels respectively, then turn on the heating device and fill with nitrogen for protection. When the system temperature rises to 25°C, open the two dropping funnels at the same time to initiate the reaction. During the reaction, use sodium hydroxide solution or nitric acid solution to control the pH value of the system at 10-13, keep the temperature at 25-40°C, and react at a constant temperature for 6-10 hours to obtain a thin film of nano calcium silicate dispersion.

[0039] The nano-calcium silicate dispersion was placed in an ultrasonic device, and after ultrasound was turned on for 20 minutes, the nano-flaky alumina dispersion was added in a mass ratio of nano-calcium silicate to nano-flaky alumina of 3:1 to obtain a dispersion of two-dimensional nanomaterials with a solid content of 15%.

[0040] To the dispersion of two-dimensional nanomaterials, a dispersion of one-dimensional nanomaterials with a solid content of 5% (made of silicon carbide, nanocellulose, silane coupling agent, polycarboxylic acid dispersant and water, the mass ratio of silicon carbide to nanocellulose is 1:1, the mass ratio of silane coupling agent to polycarboxylic acid dispersant is 2:1, and silicon carbide and nanocellulose are surface-treated with silane coupling agent and polycarboxylic acid dispersant) and a dispersion of zero-dimensional nanomaterials with a solid content of 15% (made of nano-spherical silica, multi-branched amide copolymer containing amino and carboxyl groups and water, and nano-spherical silica is surface-treated with multi-branched amide copolymer containing amino and carboxyl groups) are gradually added according to the mass ratio of 5:3:2 of the dispersion of two-dimensional nanomaterials, the dispersion of one-dimensional nanomaterials and the dispersion of zero-dimensional nanomaterials. After maintaining ultrasound for 30 to 60 minutes, a multi-dimensional nano-based functional material product is obtained, which is marked as sample #1.

[0041] Example 2

[0042] Add an appropriate amount of distilled water to a beaker, weigh 20 parts of polycarboxylic acid dispersant, 10 parts of sulfonated aldehyde ketone polycondensate dispersant, mix well, pour into a clean three-necked bottle, turn on stirring and keep the speed at 300±10r / min. Weigh 35 parts of calcium nitrate and 10 parts of calcium chloride and dissolve them in an appropriate amount of distilled water, weigh 35 parts of sodium metasilicate and dissolve them in an appropriate amount of distilled water, then add the prepared mixed solution of calcium nitrate and calcium chloride and sodium metasilicate solution to two constant pressure dropping funnels respectively, then turn on the heating device and fill with nitrogen for protection. When the system temperature rises to 25°C, open the two dropping funnels at the same time to initiate the reaction. During the reaction, use sodium hydroxide solution or nitric acid solution to control the pH value of the system at 10-13, keep the temperature at 25-40°C, and react at a constant temperature for 6-10 hours to obtain a thin film of nano calcium silicate dispersion.

[0043] The nano-calcium silicate dispersion was placed in an ultrasonic device, and after ultrasound was turned on for 20 minutes, the nano-flaky alumina dispersion was added in a mass ratio of nano-calcium silicate to nano-flaky alumina of 3:1 to obtain a dispersion of two-dimensional nanomaterials with a solid content of 18%.

[0044] To the dispersion of two-dimensional nanomaterials, a dispersion of one-dimensional nanomaterials with a solid content of 8% (made of carbon nanotubes, nanocellulose, silane coupling agent, polycarboxylic acid dispersant and water, the mass ratio of carbon nanotubes to nanocellulose is 1:1, the mass ratio of silane coupling agent and polycarboxylic acid dispersant is 2:1, and the carbon nanotubes and nanocellulose are surface-treated with silane coupling agent and polycarboxylic acid dispersant) and a dispersion of zero-dimensional nanomaterials with a solid content of 18% (made of nano-spherical alumina, multi-branched amide copolymer containing amino and carboxyl groups and water, and the nano-spherical alumina is surface-treated with multi-branched amide copolymer containing amino and carboxyl groups) are gradually added according to the mass ratio of the dispersion of two-dimensional nanomaterials, the dispersion of one-dimensional nanomaterials and the dispersion of zero-dimensional nanomaterials of 5:3:2. After maintaining ultrasound for 30 to 60 minutes, a multi-dimensional nano-based functional material product is obtained, which is marked as sample #2.

[0045] Example 3

[0046] Add an appropriate amount of distilled water to a beaker, weigh 10 parts of polycarboxylic acid dispersant and 10 parts of sulfonated aldehyde ketone condensation polymer dispersant, mix well, pour into a clean three-necked bottle, turn on stirring and keep the speed at 300±10r / min. Weigh 50 parts of calcium nitrate and 10 parts of calcium chloride and dissolve them in an appropriate amount of distilled water, weigh 30 parts of sodium metasilicate and dissolve them in an appropriate amount of distilled water, then add the prepared mixed solution of calcium nitrate and calcium chloride and sodium metasilicate solution to two constant pressure dropping funnels respectively, then turn on the heating device and fill with nitrogen for protection. When the system temperature rises to 25°C, open the two dropping funnels at the same time to initiate the reaction. During the reaction, use sodium hydroxide solution or nitric acid solution to control the pH value of the system at 10-13, keep the temperature at 25-40°C, and react at a constant temperature for 6-10 hours to obtain a thin film of nano calcium silicate dispersion.

[0047] The nano-calcium silicate dispersion was placed in an ultrasonic device, and after ultrasound was turned on for 20 minutes, the nano-flaky alumina dispersion was added in a mass ratio of nano-calcium silicate to nano-flaky alumina of 3:1 to obtain a dispersion of two-dimensional nanomaterials with a solid content of 20%.

[0048] To the dispersion of two-dimensional nanomaterials, a dispersion of one-dimensional nanomaterials with a solid content of 10% (made of silicon nanowires, polyvinyl alcohol nanofibers, silane coupling agent, polycarboxylic acid dispersant and water, the mass ratio of silicon nanowires and polyvinyl alcohol nanofibers is 1:1, the mass ratio of silane coupling agent and polycarboxylic acid dispersant is 2:1, and silicon nanowires and polyvinyl alcohol nanofibers are surface-treated with silane coupling agent and polycarboxylic acid dispersant) and a dispersion of zero-dimensional nanomaterials with a solid content of 20% (made of nano-spherical alumina, multi-branched amide copolymer containing amino and carboxyl groups and water, and nano-spherical alumina is surface-treated with multi-branched amide copolymer containing amino and carboxyl groups) are gradually added according to the mass ratio of the dispersion of two-dimensional nanomaterials, the dispersion of one-dimensional nanomaterials and the dispersion of zero-dimensional nanomaterials of 5:3:2. After maintaining ultrasound for 30 to 60 minutes, a multi-dimensional nano-based functional material product is obtained, which is marked as sample #3.

[0049] Test example

[0050] Performance evaluation of multi-dimensional nano-based functional material samples

[0051] The samples were evaluated according to the test methods specified in GB / T 19139-2012 "Test Methods for Oil Well Cement". Table 1 is the evaluation of the effects of multi-dimensional nano-based functional material samples on cement slurry rheology and thickening time, Table 2 is the evaluation of the effects of multi-dimensional nano-based functional material samples on cement slurry static gelation transition time, Table 3 is the evaluation of the effects of multi-dimensional nano-based functional material samples on cement paste strength development, and Table 4 is the evaluation of the effects of multi-dimensional nano-based functional material samples on cement paste mechanical properties.

[0052] (1) The effects of multi-dimensional nano-based functional materials 1#, 2#, and 3# samples on the rheological properties and thickening time of cement slurry were experimentally tested, and compared with the commonly used calcium chloride accelerator. The rheological test temperature was 20°C, and the thickening time test was 30°C and 50°C. The basic formula at 30°C is: G-grade cement + multi-dimensional nano-based functional material sample or calcium chloride + water (maintaining a liquid-solid ratio of 0.44). Considering the actual application situation, the formula containing fluid loss reducer was selected at 50°C: G-grade cement + multi-dimensional nano-based functional material sample or calcium chloride + 4% AMPS polymer fluid loss reducer + water (maintaining a liquid-solid ratio of 0.44). The test results are shown in Table 1.

[0053] Table 1 Effects of multi-dimensional nano-based functional material samples on cement slurry rheology and thickening time

[0054]

[0055] From the above experimental results, it can be seen that the multi-dimensional nano-based functional materials 1#, 2#, and 3# samples can significantly shorten the thickening time of cement slurry, and can improve the rheological properties of cement slurry while accelerating coagulation, overcoming the thickening problem of conventional calcium chloride and other coagulants. In addition, due to the limited thickening amount of conventional coagulants, it is difficult to effectively shorten the thickening time of cement slurry with AMPS polymer fluid loss reducer as the main agent. The product of this application can effectively shorten its thickening time without thickening.

[0056] (2) Static gelation transition time is an important indicator of the anti-channeling ability of cement slurry, and it is difficult for conventional materials to effectively shorten the static gelation transition time of cement slurry. The experiment tested the effect of multi-dimensional nano-based functional material samples 1#, 2#, and 3# on the static gelation transition time of cement slurry, and the test temperature was 30°C. The basic formula of cement slurry is: G-grade cement + multi-dimensional nano-based functional material sample + water (maintaining a liquid-solid ratio of 0.44). The test results are shown in Table 2.

[0057] Table 2 Effect of multi-dimensional nano-based functional material samples on the static gelation transition time of cement slurry

[0058]

[0059] From the above experimental results, it can be seen that the multi-dimensional nano-based functional materials 1#, 2#, and 3# samples can significantly shorten the static gelation transition time of cement slurry, and the static gelation transition time shortening rate can reach 84.0%, thereby significantly increasing the anti-channeling performance of cement slurry.

[0060] (3) The experiment tested the effects of multi-dimensional nano-based functional material samples 1#, 2#, and 3# on the early and late strength of cement paste. The test temperatures were 30°C and 50°C. The basic formula at 30°C was: G-grade cement + multi-dimensional nano-based functional material sample + water (maintaining a liquid-solid ratio of 0.44). Considering the actual application situation, the formula containing fluid loss reducer was selected at 50°C: G-grade cement + multi-dimensional nano-based functional material sample + 4% AMPS polymer fluid loss reducer + water (maintaining a liquid-solid ratio of 0.44). The test results are shown in Table 3.

[0061] Table 3 Effects of multi-dimensional nano-based functional material samples on the strength development of cement paste

[0062]

[0063]

[0064] From the above experimental results, it can be seen that the multi-dimensional nano-based functional materials 1#, 2#, and 3# samples can significantly shorten the strength-building time of cement slurry, significantly improve the early strength, and the 6h strength improvement rate can reach 421.7%. This can significantly shorten the waiting time and reduce drilling costs. In addition, unlike traditional accelerators, the 7d strength of cement paste with multi-dimensional nano-based functional materials is still significantly improved, and the strength improvement rate can reach 20.4%.

[0065] (4) The influence of multi-dimensional nano-based functional material samples 1#, 2#, and 3# on the mechanical properties of cement paste was tested using a triaxial testing machine. The cement paste was cured at 80°C for 7 days and then cored for triaxial testing. Grade G cement + multi-dimensional nano-based functional material sample + 4% AMPS polymer fluid loss reducer + 0.2% retarder + water (maintaining a liquid-solid ratio of 0.44). The test results are shown in Table 4.

[0066] Table 4 Effects of multi-dimensional nano-based functional material samples on the mechanical properties of cement paste

[0067]

[0068] From the above experiments, it can be seen that with the increase in the amount of multi-dimensional nano-based functional materials 1#, 2#, and 3# samples, the strength of cement paste gradually increases, the Young's modulus gradually decreases, and the Poisson's ratio gradually increases, showing a good strengthening and toughening effect, thereby significantly improving the anti-destruction ability of cement paste.

[0069] Experiments have shown that the multi-dimensional nano-based functional material of the present application is a multifunctional material with multiple effects in one dose. On the one hand, it can significantly shorten the thickening time of cement slurry on the basis of improving the rheological properties of cement slurry, and significantly accelerate the strength development of cement stone, thereby effectively shortening the well construction period; on the other hand, it can significantly shorten the static gelling transition time of cement slurry and reduce the probability of fluid crossflow; in addition, the multi-dimensional nano-based functional material can increase the later strength of cement stone while increasing the toughness of cement stone, thereby effectively ensuring the long-term integrity of cement stone.

[0070] The above shows and describes the basic principles, main features and advantages of the present application. Those skilled in the art should understand that the present application is not limited by the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present application. Without departing from the spirit and scope of the present application, the present application may have various changes and improvements, and the scope of protection required by the present application is defined by the attached claims, description and their equivalents.

[0071] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.

Claims

1. A multi-dimensional nano-based functional material for oil well cement, characterized in that: Including dispersions of two-dimensional nanomaterials, dispersions of one-dimensional nanomaterials and dispersions of zero-dimensional nanomaterials; The mass ratio of the dispersion of the two-dimensional nanomaterial, the dispersion of the one-dimensional nanomaterial and the dispersion of the zero-dimensional nanomaterial is 5:3:2; The solid content of the dispersion of the two-dimensional nanomaterial is 15% to 20%; The solid content of the dispersion of the one-dimensional nanomaterial is 5 to 10%; The solid content of the zero-dimensional nano material dispersion is 15% to 20%.

2. The multi-dimensional nano-based functional material for oil well cement according to claim 1, characterized in that: The dispersion of the two-dimensional nanomaterial includes a dispersion of nano calcium silicate and a dispersion of nano flaky aluminum oxide; The mass ratio of the nano calcium silicate to the nano flaky aluminum oxide is 3:1; The size of the nano calcium silicate is 50 to 100 nm; The thickness of the nano-sheet aluminum oxide is 60 to 80 nm; The nano calcium silicate dispersion is synthesized by solution precipitation method. The raw materials used for the synthesis and their weight parts are: 20-50 parts of calcium nitrate, 10-30 parts of calcium chloride, 20-50 parts of sodium metasilicate, 10-30 parts of polycarboxylic acid dispersant, and 5-10 parts of sulfonated aldehyde ketone polycondensate dispersant.

3. The multi-dimensional nano-based functional material for oil well cement according to claim 1, characterized in that: The one-dimensional nanomaterials include inorganic nanofibrous materials and organic nanofibrous materials; The inorganic nanofibrous material is selected from one or a mixture of silicon nanowires, zinc oxide nanowires, silicon carbide, and carbon nanotubes; The organic nanofibrous material is selected from one or a mixture of nanocellulose and polyvinyl alcohol nanofibers; The mass ratio of the inorganic nanofibrous material to the organic nanofibrous material is 1:1; The diameter of the one-dimensional nanomaterials is 20 to 60 nm; The one-dimensional nanomaterial in the dispersion of the one-dimensional nanomaterial is surface treated with a silane coupling agent and a polycarboxylic acid dispersant, and the mass ratio of the silane coupling agent to the polycarboxylic acid dispersant is 2:

1.

4. The multi-dimensional nano-based functional material for oil well cement according to claim 1, characterized in that: The zero-dimensional nanomaterial is selected from one or a mixture of nano-spherical silicon dioxide and nano-spherical aluminum oxide; The particle size of the zero-dimensional nanomaterial is 10 to 30 nm; The zero-dimensional nanomaterial in the dispersion of the zero-dimensional nanomaterial is surface treated with an amide copolymer containing amino groups and carboxyl groups. The relative molecular weight of the amide copolymer containing amino groups and carboxyl groups is 120,000-150,000, and the molecular weight distribution index is 2.0-2.

2.

5. The multi-dimensional nano-based functional material for oil well cement according to claim 2 or 3, characterized in that: The relative molecular weight of the polycarboxylic acid dispersant is 60,000 to 100,000, and the molecular weight distribution index is 1.5 to 1.7.

Citation Information

Patent Citations

  • Preparation method of polyacrylamide nano composite fracturing fluid

    CN104109525A

  • Weak coagulation type early strength agent for oil well cement

    CN109880604A

  • Nanometer anti-channeling agent and preparation method thereof, and anti-channeling cement paste

    CN111704389A

  • Crystal nucleus-based composite coagulation-accelerating early strength agent for oil well cement and preparation method of crystal nucleus-based composite coagulation-accelerating early strength agent

    CN116143440A